2018
DOI: 10.3329/bpj.v21i2.37919
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bacterial Contamination of Dried Herbs and Spices Collected from Street Markets in Dhaka

Abstract: Crude plant parts used as a source of medicine is an ancient practice and important for health care system worldwide. In Bangladesh, a large number of population depends on the traditional medicine using crude drugs. In traditional systems, street sellers collect powered plant parts or dried plant parts from whole sale markets locally or from various parts of Bangladesh. Favorable environmental condition for microbial growth and handling with unhygienic conditions may result in microbial contamination. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Most of the tested samples exceeded the upper permissible limit of bacterial count (>10 5 cfu∙g −1 ). The performed study confirms literature reports that herbs available on the market are highly contaminated by microorganisms [ 33 , 34 ]. Cold plasma pre-treatment showed a germicidal property for most extracts.…”
Section: Resultssupporting
confidence: 89%
“…Most of the tested samples exceeded the upper permissible limit of bacterial count (>10 5 cfu∙g −1 ). The performed study confirms literature reports that herbs available on the market are highly contaminated by microorganisms [ 33 , 34 ]. Cold plasma pre-treatment showed a germicidal property for most extracts.…”
Section: Resultssupporting
confidence: 89%
“…Almost 50% of the herbs did not exceed the aerobic mesophilic level of 10 4 cfu/g (4 log cfu/g) in a study conducted on 99 samples of aromatic herbs collected from retail shops across Algarve, Southern Portugal [63]. Nur and coauthors [64] found that 13 out of 33 samples (dried herb and spice) from Dhaka, Bangladesh exceeded the permissible limit of bacterial count (>10 5 cfu/g/5 log cfu/g). However, 20 samples showed bacterial count ranging between 3.1 × 10 2 and 2 × 10 3 cfu/g (2.49-3.30 log cfu/g) [64].…”
Section: Discussionmentioning
confidence: 99%
“…Nur and coauthors [64] found that 13 out of 33 samples (dried herb and spice) from Dhaka, Bangladesh exceeded the permissible limit of bacterial count (>10 5 cfu/g/5 log cfu/g). However, 20 samples showed bacterial count ranging between 3.1 × 10 2 and 2 × 10 3 cfu/g (2.49-3.30 log cfu/g) [64]. The aerobic mesophilic microorganisms did not exceed 10 5 cfu/g in most of 46 samples of the aromatic herbs from Algarve, Portugal [65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations